1993
DOI: 10.1128/jcm.31.4.963-967.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three enzyme immunoassays, a cytotoxicity assay, and toxigenic culture for diagnosis of Clostridium difficile-associated diarrhea

Abstract: Enzyme immunoassays (EIAs) based on monoclonal antibodies for the detection of Clostridium difficile toxins have recently been developed for clinical use. The aim of this study was to compare three commercially available EIAs, two for toxin A (Premier C. difficile Toxin A; Meridian, Osi, Elancourt, France; and Vidas C. difficik Toxin A; bioMerieux, Marcy l'Etoile, France) and one for toxins A and B (Cytoclone A + B EIA; Cambridge Biotech Corp., Codiapharm, Evian, France), with a cytotoxicity assay and toxigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Our results are parallel to this finding. The reported sensitivity and specificity values for other available commercial EIA kits which can detect toxins A and B were between 79.6 and 96.2%, 93.5 and 100%, respectively, and PPV and NPV were between 86.7 and 100% and 95.7 and 99%, respectively [14,18,20,21]. These results are similar to, or a little lower than, those obtained for the Techlab A/B test.…”
Section: Discussionsupporting
confidence: 69%
“…Our results are parallel to this finding. The reported sensitivity and specificity values for other available commercial EIA kits which can detect toxins A and B were between 79.6 and 96.2%, 93.5 and 100%, respectively, and PPV and NPV were between 86.7 and 100% and 95.7 and 99%, respectively [14,18,20,21]. These results are similar to, or a little lower than, those obtained for the Techlab A/B test.…”
Section: Discussionsupporting
confidence: 69%
“…16 The study recruited consecutive hospitalized patients with CDI, which was defined as diarrhea and a positive toxin test for C. difficile using the cytotoxicity assay. 17 Diarrhea was defined as three or more loose bowel movements within a 24-hour period. The study protocol was approved by the institutional review board at the hospital.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…40 Results of this test are generally reported within hours or within 1 day. [41][42][43] Culturing stool, if done correctly, has a high degree of sensitivity for identifying the organism, but lacks specificity in relating the presence of C. difficile to disease. Many patients may be colonized with C. difficile and yet remain free of disease.…”
Section: Diagnosismentioning
confidence: 99%
“…In vitro, C. difficile is susceptible to vancomycin; the minimum inhibitory concentration (MIC) for 90% of tested strains (MIC 90 ) is 0.75-2 µg/ml. 41,[49][50][51][52][53][54] A single study found that 3% of C. difficile isolates had intermediate resistance to vancomycin (MIC 4-16 µg/ml), but the clinical implications were not reported, and the in vitro findings have not been reproduced. 55 Since oral vancomycin leads to stool concentrations of up to 3100 µg/ml, 56 results of this study are not likely to be clinically significant.…”
Section: Vancomycinmentioning
confidence: 99%